Studies on the physicochemical, biomechanical and biological properties of novel decellularized bovine scaffold for bone regeneration - Qabbani, Ali Abdul Qader Hameed Al (2024)
Bone grafting, the second most common transplant practice after blood transfusion, involves significant challenges in transferring xenogeneic donor bone cells to recipients due to potential immunological responses. This study aimed to explore the efficacy of producing bovine cancellous bone scaffolds by preserving the extracellular matrix (ECM) while eliminating native bone cells, comparing their physicochemical, mechanical, and biological properties with demineralized cancellous bone scaffolds. The study was conducted in three phases. In Phase I, cancellous bone blocks harvested from the bovine femoral head were physically cleansed, chemically defatted, and processed into two types of scaffolds: demineralized bovine cancellous bone (DMB) and decellularized bovine cancellous bone (DCC). Both scaffolds were freeze-dried and gamma-radiated. Various analyses, including histology, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Fourier-transform infrared spectroscopy, were performed to evaluate the scaffolds. Recellularization studies was done using human osteoblast cells showed that DCC scaffolds produced a complete acellular ECM with wider pores, retained collagen fibrils, and exhibited better cell attachment, proliferation, and mineralization compared to DMB. In Phase II, the immuno-compatibility of DMB and DCC scaffolds was tested in male Balb/c mice models following peritoneal implantation. The results revealed that DCC scaffolds elicited significantly lower white blood cell counts and systemic inflammation compared to DMB and untreated native bone. Immunotoxicity analyses showed that the DMB group had higher CD4+ counts and increased pro-inflammatory cytokine expression, while the DCC group exhibited a more favourable immune response, with more CD8+ T cells and normal organ morphology, indicating better immuno-compatibility. Phase III focused on the bone regeneration capabilities of DMB and DCC scaffolds in male Sprague-Dawley rat calvarial critical-size defects. The study found that DCC scaffolds significantly promoted new bone formation, with enhanced defect closure and higher bone density observed in micro-CT analyses compared to DMB. DCC sites also demonstrated elevated mRNA levels of osteogenic markers such as osteonectin, osteopontin, and osteocalcin. RAMAN spectroscopy showed an increased abundance of collagen and bone minerals, particularly phosphate ions (PO43-), in DCC scaffolds. In conclusion, the decellularization technique effectively produced an acellular DCC scaffold with minimal ECM damage and superior osteogenic potential in both in vitro and in vivo models. DCC scaffolds demonstrated better immuno-compatibility and greater bone regeneration potential than DMB, making them a promising option for bone grafting applications.